Organizational Climate Transformation and Emerging Implications for Teacher Job Satisfaction - Zikrayati, Zikrayati; Usman, Nasir; AR, Murniati (JURNAL AL-TANZIM, 2025)
This study aims to investigate how organisational climate transformation can enhance teacher job satisfaction in two public high schools. The approach used in this study was a descriptive qualitative one, with data collected through interviews, observations, and documentation involving principals and teachers. A total of six participants were selected using purposive sampling techniques to ensure the relevance and depth of information. This study demonstrates that both schools have developed participatory and transformative organisational climates, where principals engage teachers in program planning through consultative forums and collaborative work teams. One school focuses on teacher training and reflection twice a year, while the other implements monthly evaluations supported by a humanistic leadership approach. Both schools emphasise teacher participation, open communication, recognition, and ongoing evaluation to enhance job satisfaction. These findings support the notion that organisational climate transformation through active teacher involvement is efficacious in improving professionalism and educational quality, and provide theoretical and practical contributions to school leadership development and policy. This study provides important implications for the development of school leadership practices, demonstrating that active teacher involvement in organisational climate transformation can enhance job satisfaction and professionalism.